Sources of Economic Fluctuations in Central America - Toledo, Wilfredo (Universidad EAFIT, 2018)
sing panel data from Central America, this paper studies the determining factors of inflation and aggregate output fluctuations by estimating two Structural Vector Autoregressive (SVAR) models. Price and output variables are included in one of the models, whereas M2 and the price of oil are additional variables in the other one. Findings of this study suggest that price is determined by the demand, while output seems to be influenced mainly by the supply shocks in that area. It was also evidenced that the price of oil does not have a significant impact on the general price level in that region.